C.E. Credit. Elevating the Conversation: Safety and Risk Management in Dental Practice - Ronald R. Zentz (Taylor & Francis Group, 2024)
Beginning in the 1970s and 1980s, risk management principles were adapted to healthcare from other industries to help address the proliferation of medical malpractice settlements and judgments. Efforts focused on Identifying and mitigating legal vulnerabilities. As dentists continue to refine and expand services offered to their patients, they must assess and proactively address potential risks for the benefit of patients and professional liability mitigation. This article will consider the recent past and status of patient safety and risk management in dentistry, as well as immediate opportunities for safety improvements and risk mitigation in professional dental practice. Although individual dentists and dental practices may identify and implement methods to improve safety and risk management, cooperative dental professional and cross-professional initiatives will help to foster change more broadly, benefitting both dental patients and all dental professionals.Continuing Education Credit Available: The practice worksheet is available online in the supplemental material tab for this article. A CDA Continuing Education quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20